(untitled) (Journal of Information Technologies in Education (ITE), 2013)
Results on modeling of electronic information resources of training on the basis of Wikitechnologies are presented. Application of such model is illustrated on an example of working out of the program module of distance learning system «Kherson virtual university» for creation and use of Wiki-documents.